G. Giuliano, P. De Simone, Paisiello e la Russia, Lettere al Conte Voroncov, Valore Italiano Editore, Roma 2024 (= Correnti d’incontro tra Russia ed Europa), pp. 251. - Anna Giust (Studi Slavistici, 2025)
Book Review